Overexpression, crystallization and preliminary X‐ray crystallographic analysis of the variable lymphocyte receptor 2913 ectodomain fused with internalin B. Issue 1 (8th January 2013) - Lee, Ji Yeon; Kim, Hyoun Sook; Baek, In Wha; Back, Jang Mi; Han, Mi Ra; Kong, Sun‐Young; Kim, Ji Hyeon; Kirchdoerfer, Robert N.; Kim, Jae‐Ouk; Cooper, Max D.; Wilson, Ian A.; Kim, Hyun‐Jung; et al.
<x xml:space="preserve">Abstract</x> In jawless vertebrates, variable lymphocyte receptors (VLRs) play a crucial role in the recognition of antigens as part of the adaptive immune system. Leucine‐rich repeat (LRR) modules and the highly variable insert (HVI) of VLRs contribute to the specificity and diversity of antigen recognition. VLR2913, the antigen of which is not known, contains the same HVI amino‐acid sequence as that of VLR RBC36, which recognizes the H‐trisaccharide from human blood type O erythrocytes. Since the HVI sequence is rarely identical among all known VLRs, identification of the antigen for VLR2913 and the main contributing factors for antigen recognition based on a comparison of VLR2913 and VLR RBC36 has been attempted. To initiate and facilitate this structural approach, the ectodomain of VLR2913 was fused with the N‐terminal domain of internalin B (InlB‐VLR2913‐ECD). Three amino‐acid residues on the concave surface of the LRR modules of InlB‐VLR2913‐ECD were mutated, considering important residues for hydrogen bonds in the recognition of H‐trisaccharide by VLR RBC36. InlB‐VLR2913‐ECD was overexpressed in Escherichia coli and was crystallized at 295 K using the sitting‐drop vapour‐diffusion method. X‐ray diffraction data were collected to 2.04 Å resolution and could be indexed in the tetragonal space group P41212 (or P43212), with unit‐cell parameters a = 91.12, b = 91.12, c = 62.87 Å. Assuming that one monomer molecule was present in the crystallographic asymmetric unit, the calculated Matthews coefficient (VM) was 2.75 Å3 Da−1 and the solvent content was 55.2%. Structural determination of InlB‐VLR2913‐ECD by molecular replacement is in progress.